The human adaptor SARM negatively regulates adaptor protein TRIF-dependent Toll-like receptor signaling - Carty, Michael (My University, 2006)
Toll-like receptors discriminate between different pathogen-associated molecules and activate signaling cascades that lead to immune responses. The specificity of Toll-like receptor signaling occurs by means of adaptor proteins containing Toll-interleukin 1 receptor (TIR) domains. Activating functions have been assigned to four TIR adaptors: MyD88, Mal, TRIF and TRAM. Here we characterize a fifth TIR adaptor, SARM, as a negative regulator of TRIF-dependent Toll-like receptor signaling. Expression of SARM blocked gene induction 'downstream' of TRIF but not of MyD88. SARM associated with TRIF, and 'knockdown' of endogenous SARM expression by interfering RNA led to enhanced TRIF-dependent cytokine and chemokine induction. Thus, the fifth mammalian TIR adaptor SARM is a negative regulator of Toll-like receptor signaling.
PUBLISHED
Keywords: Immunology, Inflammation & Infection; Toll-Like Receptors